The experience of being parents of mixed-heritage children: phenomenological analysis - Bratawidjaja, Andrew (Kansas State University, 2007)
Cross-national phenomenon is often cloaked behind the shadow of interracial phenomenon. This study specifically focused on the cross-national phenomenon, especially the couples' experience as parents of their mixed-heritage child. In the process of exploration, both the couples' marital and parenting experience were captured. By employing a qualitative approach and analysis, eight cross-national couples who lived in the Midwest were recruited and interviewed about their parenting experience. The interviews were transcribed verbatim, coded and analyzed. The results of the study produced five categories of cross-national couples' experience: perceptions, relational dynamics, parent/child relationship issues, contextual influences, and essential coping strategies. By utilizing systemic perspectives, the descriptive findings were further analyzed in order to describe the potential interactions among categories, themes, and concepts. The analysis revealed five essential domains that were integral to the couples' cross-national parenting experience including, the individual domain, the couple domain, the child domain, the environmental domain, and the parenting domain. It is evident that the majority of cross-national couples did not always perceive their relational context in term of being mixed or cross-national but rather simply as couple or parent. It was not until the birth of their children that couples typically began to face the reality of being cross-national couples. Participants identified both unique strengths and challenges of being parents of mixed-heritage children. The findings suggested that the experience of cross-national parents are both common as well as unique, shaped by the multifaceted domains and their interactions. The systemic analysis revealed those idiosyncratic domains and factors within those domains. Although all of these domains appeared equally significant in contributing to the parenting quality and experience, the couple, the parenting and the environmental domains appeared to have the greatest influence. The more couples work toward cohesion and harmony in the different domains of their lives, the more favorable their experience was. Clinical implications for therapists working with cross-national couples and parents, utilizing the systemic framework, are discussed. Recommendations for future studies are also presented.
Keywords: Cross-national marriage; Cross-national parenting; Parents of mixed-heritage children; Sociology, Ethnic and Racial Studies (0631); Sociology, Individual and Family Studies (0628)